1999
DOI: 10.1104/pp.119.3.1107
|View full text |Cite
|
Sign up to set email alerts
|

Nicotianamine Chelates Both FeIII and FeII. Implications for Metal Transport in Plants1

Abstract: -dependent oxidation of deoxyribose. This suggests that NA will have an important role in scavenging Fe and protecting the cell from oxidative damage. The pH dependence of metal ion chelation by NA and a typical phytosiderophore, 2 -deoxymugineic acid, indicated that although both have the ability to chelate Fe, when both are present, 2 -deoxymugineic acid dominates the chelation process at acidic pH values, whereas NA dominates at alkaline pH values. The consequences for the role of NA in the long-distance tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
344
0
4

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 426 publications
(367 citation statements)
references
References 32 publications
18
344
0
4
Order By: Relevance
“…The sensing mechanisms are not known, but the metal chelator nicotianamine is important for Fe homestasis 35,36 and can bind both Fe and Cu. 37 We also showed that under Fe deficiency, plants were strikingly more susceptible to Cu toxicity. Understanding this aspect of Fe-Cu crosstalk could have implications for agriculture and for phytoremediation of metal contaminated soils.…”
mentioning
confidence: 76%
“…The sensing mechanisms are not known, but the metal chelator nicotianamine is important for Fe homestasis 35,36 and can bind both Fe and Cu. 37 We also showed that under Fe deficiency, plants were strikingly more susceptible to Cu toxicity. Understanding this aspect of Fe-Cu crosstalk could have implications for agriculture and for phytoremediation of metal contaminated soils.…”
mentioning
confidence: 76%
“…This unusual chlorosis pattern may be the result of a redistribution of the cytoplasmic NA pool to the chloroplast. This has the dual effect of restricting NA from performing its role in phloem transport of iron and other metals (von Wiren et al, 1999) and also sequestering iron itself, thus preventing it from being redistributed throughout the plant body. Iron, applied in excess (300 mM), is able to rescue the chlorosis phenotype, and the MAR1 gene is down-regulated under iron deficiency to prevent sequestration of needed iron.…”
Section: Discussionmentioning
confidence: 99%
“…NA is also thought to play an important role in the detoxification of excess intracellular Fe (von Wirén et al, 1999). NA concentrations in tomato increase in response to Fe overload (Pich et al, 2001).…”
Section: Two Different Expression Patterns With Different Localizationmentioning
confidence: 99%